Dystrophin Gene Mutation Location and the Risk of Cognitive Impairment in Duchenne Muscular Dystrophy - Taylor, Peter J. (Public Library of Science, 2010)
BACKGROUND: A significant component of the variation in cognitive disability that is observed in Duchenne muscular dystrophy (DMD) is known to be under genetic regulation. In this study we report correlations between standardised measures of intelligence and mutational class, mutation size, mutation location and the involvement of dystrophin isoforms. METHODS AND RESULTS: Sixty two male subjects were recruited as part of a study of the cognitive spectrum in boys with DMD conducted at the Sydney Children's Hospital (SCH). All 62 children received neuropsychological testing from a single clinical psychologist and had a defined dystrophin gene (DMD) mutation; including DMD gene deletions, duplications and DNA point mutations. Full Scale Intelligence Quotients (FSIQ) in unrelated subjects with the same mutation were found to be highly correlated (r = 0.83, p = 0.0008), in contrast to results in previous publications. In 58 cases (94%) it was possible to definitively assign a mutation as affecting one or more dystrophin isoforms. A strong association between the risk of cognitive disability and the involvement of groups of DMD isoforms was found. In particular, improvements in the correlation of FSIQ with mutation location were identified when a new classification system for mutations affecting the Dp140 isoform was implemented. SIGNIFICANCE: These data represent one of the largest studies of FSIQ and mutational data in DMD patients and is among the first to report on a DMD cohort which has had both comprehensive mutational analysis and FSIQ testing through a single referral centre. The correlation between FSIQ results with the location of the dystrophin gene mutation suggests that the risk of cognitive deficit is a result of the cumulative loss of central nervous system (CNS) expressed dystrophin isoforms, and that correct classification of isoform involvement results in improved estimates of risk.